Encapsulation of Pink Pepper Essential Oil (Schinus terebinthifolius Raddi) in Albumin and Low-Methoxyl Amidated Pectin Cryogels - Chaux-Gutiérrez, Ana María [UNESP]; Pérez-Monterroza, Ezequiel José [UNESP]; Cattelan, Marília Gonçalves [UNESP]; Nicoletti, Vânia Regina [UNESP]; Moura, Márcia Regina de [UNESP] (MDPI, 2024)
This study evaluated cryogels from albumin (ALB) and albumin–pectin (ALB:PEC) as carriers for pink pepper (Schinus terebinthifolius Raddi) essential oil. Cryogels were evaluated through infrared spectrophotometry, X-ray diffraction, scanning electron microscopy, thermogravimetric analysis, and differential scanning calorimetry. The bioactivity of the cryogels was analyzed by measuring their encapsulation efficiency (EE%), the antimicrobial activity of the encapsulated oil against S. aureus, E. coli, and B. cereus using the agar diffusion method; total phenolic content and antioxidant activity were analyzed by UV-vis spectrophotometry. The EE% varied between 59.61% and 77.41%. The cryogel with only ALB had the highest total phenolic content with 2.802 mg GAE/g, while the cryogel with the 30:70 ratio (ALB:PEC) presented a value of 0.822 mg GAE/g. A higher proportion of PEC resulted in a more significant inhibitory activity against S. aureus, reaching an inhibition zone of 18.67 mm. The cryogels with ALB and 70:30 ratio (ALB:PEC) presented fusion endotherms at 137.16 °C and 134.15 °C, respectively, and semicrystalline structures. The interaction between ALB and PEC increased with their concentration, as evidenced by the decreased intensity of the O-H stretching peak, leading to lower encapsulation efficiency. The cryogels obtained can be considered a suitable matrix for encapsulating pink pepper oil.
Keywords: antimicrobial activity; biopolymers; phenolic compounds; polysaccharides; S. aureus